The specific heat loss combined with the thermoelastic effect for an experimental analysis of the mean stress influence on axial fatigue of stainless steel plain specimens (Fracture and Structural Integrity, 2014)
The energy dissipated to the surroundings as heat in a unit volume of material per cycle, Q, was recently proposed by the authors as fatigue damage index and it was successfully applied to correlate fatigue data obtained by carrying out fully reversed stress- and strain-controlled fatigue tests on AISI 304L stainless steel plain and notched specimens. The use of the Q parameter to analyse the experimental results led to the definition of a scatter band having constant slope from the low- to the high-cycle fatigue regime. In this paper the energy approach is extended to analyse the influence of mean stress on the axial fatigue behaviour of unnotched cold drawn AISI 304L stainless steel bars. In view of this, stress controlled fatigue tests on plain specimens at different load ratios R (R=-1; R=0.1; R=0.5) were carried out. A new energy parameter is defined to account for the mean stress effect, which combines the specific heat loss Q and the relative temperature variation due to the thermoelastic effect corresponding to the achievement of the maximum stress level of the stress cycle. The new two-parameter approach was able to rationalise the mean stress effect observed experimentally. It is worth noting that the results found in the present contribution are meant to be specific for the material and testing condition investigated here.
Keywords: Dissipated energy density